New records of digeneans from Podocnemis spp. (Testudines, Podocnemididae) from Iquitos, Peru - Tantaleán, Manuel (2011)
We obtained 8 digestive tract of the turtle Podocnemis expansa and 18 of P. unifilis from the Belen market (Iquitos, Peru). Only digeneans were studied and identified. Four species were found: Nematophila grandis (Diesing, 1839) Travassos, 1934, Halltrema avitellina Lent & Freitas, 1939, Podocnemitrema papillosum Alho & Vicente, 1964 and Telorchis hagmanni Lent & Freitas, 1937. Halltrema avitellina, Podocnemitrema papillosum and Telorchis hagmanni are new records from Peru.